2007
DOI: 10.1614/ws-06-168
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Nonindigenous Weed Species by Their Potential to Invade the United States

Abstract: Because of the large number of potentially invasive species, and the time required to complete weed risk assessments (WRAs) with the use of the current, mandated system in the United States, species need to be prioritized for assessment and possible listing as Federal Noxious Weeds. Our objective was to rank the potential invasiveness of weedy or pest plant species not yet naturalized in the United States. We created a new model of invasiveness (hereafter the U.S. weed-ranking model) based on scoring factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…The mean number of questions was 22 and the median was 17. The Australian WRA model involves a relatively large number of questions so as to reduce the need for subsequent evaluation (Parker et al 2007). Generally, it can be argued that the higher is the number of questions, the more precise is the outcome of the model, and the more difference there will be in the total scores of the organisms.…”
Section: Number Of Questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean number of questions was 22 and the median was 17. The Australian WRA model involves a relatively large number of questions so as to reduce the need for subsequent evaluation (Parker et al 2007). Generally, it can be argued that the higher is the number of questions, the more precise is the outcome of the model, and the more difference there will be in the total scores of the organisms.…”
Section: Number Of Questionsmentioning
confidence: 99%
“…For instance, if the probability of entry is zero, then the total score is zero as well. In an additive model it is possible that the total score is still relatively high, although for instance habitat suitability might be very low (Parker et al 2007, Cox 2009). Makowski and Mittinty (2010) simulated the outcome of several scoring systems and showed that multiplication-based systems performed better than sum-based systems.…”
Section: Point Scales Score Aggregation and Weightingmentioning
confidence: 99%
See 3 more Smart Citations